Broadening psychology's contribution to addressing issues of HIV/AIDS, poverty and nutrition: Structural issues as constraints and opportunities - Tomlinson, Mark; Rohleder, Poul; Swartz, Leslie; Drimie, Scott; Kagee, Ashraf (SAGE Publications, 2010)
HIV/AIDS, more than any other public health problem, challenges dominant models of the role of psychology in health promotion and prevention. This paper focuses on poverty and resulting food insecurity as a structural risk factor for HIV infection. The paper considers the role of health psychology in global health concerns and argues that, while individual-based interventions are important, health psychology needs to shift to playing a proper role in broader level initiatives. Health psychology, in thinking about global health concerns such as HIV, needs to view an understanding of health, education and nutrition delivery programmes in low resourced contexts as at the core of the discipline.